Relationship Pattern among Scientific Literacy, Thematic, and Scientific Materials in Online Learning - Sufiyanto, Mohammad Imam; Jamilah, Jamilah; Hikmawati, Nisrina (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The purpose of this study is to determine the relationship among scientific, thematic learning materials, and scientific literacy integrated in online learning carried out in three different primary schools, namely MI Al-Ikhlas, Luqman Al-Hakim Integral Elementary School, and at Madrasah Ibtidaiyah Negeri (MIN) 1 Sumenep in Sumenep Regency. Learning scienceÂ is with a scientific approach in primary school can be meant as student's mastery of knowledge about scientific, thematic, and scientific literacy, which is learned from facts, principles, and the discovery process during online learning. However, the science material given must be adapteded to the age and characteristics of the students concerned, meaning that science material is given to students and adjusted to the grade level, so that mastery of science can be beneficial both for the students and for the natural environment preservationÂ around them. The method used in this research is descriptive qualitative research with a survey approach. The research population was 60 teachers and 280 students from three different schools, while the sample of this study consisted of 30 teachers and 150 students from whom the samples were taken using probability sampling. The data collection techniques in this study were in the forms of questionnaires and interview techniques for the teachers and students to complete the data. The research results showed that in the aspect of scientific literacy, namely explaining problems scientifically was 29.5%, interpreting data scientifically was 19%, communicating data scientifically was 40%, planning scientific investigations was 29.5%, carrying out scientific investigations was 33 %, and evaluated scientific investigations was 19%. These data indicate that there are still problems in the application of scientific, thematic, and scientific literacy during the pandemic period for students and thus, requires follow-up for solution